2017
DOI: 10.1099/jmmcr.0.005085
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of Listeria monocytogenes prosthetic valve endocarditis using rifampicin and benzylpenicillin in combination with valve replacement

Abstract: Introduction. Listeria monocytogenes is an uncommon cause of prosthetic valve endocarditis (PVE). Recommended antimicrobial therapy typically includes intravenous β-lactams with or without synergistic aminoglycosides. In vitro studies have previously identified antagonism when rifampicin has been used in combination with β-lactams. However, in vivo data of rifampicin use are limited despite its enhanced anti-biofilm activity.Case presentation. A 63-year-old male presented with fever and back pain. L. monocytog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…Following ingestion, systemic infection can be established through tissue penetration across the gastrointestinal tract or hematogenous spread to sterile sites including the central nervous system (CNS), heart, liver, spleen, and placenta [ 3 ]. Consistent with this, L. monocytogenes associated bacteremia, meningoencephalitis, infective endocarditis, and endovascular graft infections have been previously reported [ 4 7 ]. Interestingly, however, this organism rarely causes bone and joint infections, and if so, occurs typically in the context of prosthetic material providing a site for bacterial seeding.…”
Section: Introductionsupporting
confidence: 85%
“…Following ingestion, systemic infection can be established through tissue penetration across the gastrointestinal tract or hematogenous spread to sterile sites including the central nervous system (CNS), heart, liver, spleen, and placenta [ 3 ]. Consistent with this, L. monocytogenes associated bacteremia, meningoencephalitis, infective endocarditis, and endovascular graft infections have been previously reported [ 4 7 ]. Interestingly, however, this organism rarely causes bone and joint infections, and if so, occurs typically in the context of prosthetic material providing a site for bacterial seeding.…”
Section: Introductionsupporting
confidence: 85%
“…The authors present a case of a 65-year-old male with a past medical history of diabetes mellitus, alcohol consumption and recurrent skin abscess who was diagnosed with a perianal abscess due to Listeria monocytogenes , with associated lumbar spine osteitis. Performing a PubMed search with terms “listeriosis”, “ Listeria monocytogenes ” and “spondylodiscitis” just two related cases of spondylodiscitis due to Listeria monocytogenes were found: the first one in an elderly man without other predisposing risk factors other than his advanced age [11]; and the second one in a 63-year-old man with medical history of type 2 diabetes mellitus without other risk factors, who presented with both spondylodiscitis and endocarditis [12].…”
Section: Introductionmentioning
confidence: 99%
“…Spinal involvement is less common, resulting in spondylodiscitis. To our knowledge, 7 cases of Listeria spondylodiscitis have been described in the literature (Table 1) [4,9,10,11,12,13,14]. In some cases, the diagnosis was confirmed by spinal biopsy.…”
Section: Discussionmentioning
confidence: 98%
“…In a 2012 study, no treatment failure was observed in patients with the osteoarticular form without prosthetic devices treated for a median of 15 weeks [7]. Other authors have shown the effectiveness of rifampicin and cotrimoxazole [4,11]. Long-term treatment with aminopenicillin remains a consensus.…”
Section: Discussionmentioning
confidence: 99%